Different prostaglandin F2α secretion in response to oxytocin injection between pregnant and non‐pregnant cows: effect of the day of oxytocin challenge test for determining the difference. (27th November 2017) - Kubo, Tomoaki; Iga, Kosuke; Fukuju, Naoki; Kizaki, Keiichiro; Osawa, Takeshi; Izaike, Yoshiaki; Takahashi, Toru
Abstract: The present study was conducted to determine the difference in plasma prostaglandin F2 α metabolite concentrations following oxytocin (OT) challenge between pregnant and non‐pregnant cows. Experiment 1: cows were subjected to the OT challenge test on days 12, 14 or 16 (day of estrus = day 0) with or without prior insemination and plasma 13, 14‐dihydro‐15‐keto prostaglandin F2 α (PGFM) concentrations were measured from −30 to 180 min after OT injection. On day 16, the increment of plasma PGFM concentrations in response to OT injection was significantly smaller in pregnant than that in cyclic cows. On days 12 and 14, there was little OT‐induced PGFM secretion and no difference in PGFM increase between the pregnant and cyclic cows. Experiment 2: cows were inseminated on day 0 and subjected to the OT challenge test on day 16. Cows were classified into non‐pregnant/early embryonic death (NP/EED), late embryonic death (LED) and pregnant (PREG) groups. The increment of PGFM concentrations in response to OT injection was less in both PREG and LED groups than that in the NP/EED group. In conclusion, plasma PGFM secretion induced by OT is suggested as the base of pregnancy diagnosis prior to returning estrus in cows.